2022
DOI: 10.1155/2022/7890338
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioma of the Lower Lip—A Diagnostic Dilemma: Report of a Rare Case with a Brief Literature Review

Abstract: Hamartomas are tumor-like deformities typified by cellular propagation indigenous to the original site, although they display growth arrest without the possibility for further growth. Various hamartomatous oral lesions include hemangiomas, lymphangiomas, nevi, odontomas, Cherubism, etc. Lymphangiomas are benign, developmental hamartomatous entities typified by abnormal proliferation of lymphatic vessels. They are usually congenital, and more than 90% of cases occur by 2 years of age, with a rare occurrence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…18 Hasan et al reported a case of lymphangioma of the lower lip and also reviewed 16 more cases of lymphangioma of lower lip, buccal mucosa, neck and submandibular region. 19 In our study, 7 cases of lymphangioma were found in head and neck region and 1 case occurred over chest. Surgical excision is the treatment of choice.…”
Section: Discussionmentioning
confidence: 49%
“…18 Hasan et al reported a case of lymphangioma of the lower lip and also reviewed 16 more cases of lymphangioma of lower lip, buccal mucosa, neck and submandibular region. 19 In our study, 7 cases of lymphangioma were found in head and neck region and 1 case occurred over chest. Surgical excision is the treatment of choice.…”
Section: Discussionmentioning
confidence: 49%
“…3 The major differential diagnosis of superficial lymphangioma in adults is an acquired lymphangiectasia caused by secondary damage to the normal lymphatic channels. 1,6 Lymphangioma and acquired lymphangiectasia are histologically almost identical. The histologic differential diagnosis points include complete endothelial lining and sequestered lymphatic cistern in the subcutis with a smooth muscle layer that can be observed in lymphangioma.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of the mass being a mucocele may be negated by the site and age of the patient (mucoceles are more likely to occur on the lower lip of children and young adults) and a chronic duration of 3.5 years. The possibility of salivary duct cysts is highly unlikely as they characteristically appear as bluish, firm nodular swellings on the floor of the mouth and rarely on the lips [ 23 , 24 ]. The diagnosis of a malignant minor salivary gland tumor (adenoid cystic carcinoma and acinic cell carcinoma) may be ruled out based on the location, well-circumscribed mass, chronic duration, and lack of fixation [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of salivary duct cysts is highly unlikely as they characteristically appear as bluish, firm nodular swellings on the floor of the mouth and rarely on the lips [ 23 , 24 ]. The diagnosis of a malignant minor salivary gland tumor (adenoid cystic carcinoma and acinic cell carcinoma) may be ruled out based on the location, well-circumscribed mass, chronic duration, and lack of fixation [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%